2015
DOI: 10.1093/infdis/jiv332
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccination Enhances the Immunogenicity of Subsequent Influenza Vaccination in Healthy Volunteers: A Randomized, Placebo-Controlled Pilot Study

Abstract: BCG vaccination prior to influenza vaccination results in a more pronounced increase and accelerated induction of functional antibody responses against the 2009 pandemic influenza A(H1N1) vaccine strain. These results may have implications for the design of vaccination strategies and could lead to improvement of vaccination efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
191
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(212 citation statements)
references
References 29 publications
13
191
1
1
Order By: Relevance
“…Protective role of BCG against influenza infections in mice and unintended beneficial effects of BCG vaccinations in humans have been demonstrated by others [12,13]. BCG’s non-specific protections against other diseases are mostly through enhancement of macrophage recruitment and function in the site of infection [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective role of BCG against influenza infections in mice and unintended beneficial effects of BCG vaccinations in humans have been demonstrated by others [12,13]. BCG’s non-specific protections against other diseases are mostly through enhancement of macrophage recruitment and function in the site of infection [14].…”
Section: Discussionmentioning
confidence: 99%
“…BCG also confers a non-specific protection against influenza infections in mice [12]. Substantial evidences for nonspecific beneficial effects of BCG vaccination in humans have been provided by a randomized clinical trial [13]. BCG increases non-specific protection against other diseases mostly through enhancement of macrophage functions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while polyclonal stimulation of B cell responses could contribute to sustained antibody responses throughout life, the evidence for this is inconsistent. When given at or around the same time as other vaccines, BCG may enhance the antibody response to those vaccines, acting as or like an adjuvant, although the specific effects/outcomes are a matter of debate 29-31 . In any case, this is not likely to be the main mechanism for the beneficial heterologous effects of BCG or measles vaccine in infants because they often lack pre-existing immunity to most pathogens and durability of antibody responses is more limited than at older ages, perhaps attributable in part to suboptimal support in the bone marrow 32, 33 .…”
Section: Heterologous Lymphocyte Responsesmentioning
confidence: 99%
“…BCG vaccine has been associated in multiple studies with effects beyond protection against tuberculosis, which is the original target of the intervention (1). As such, BCG vaccination has been shown to enhance the protection provided by H1N1 vaccine (2). Another study observed that prior BCG vaccination attenuates yellow fever vaccine associated viremia (3).…”
Section: Introductionmentioning
confidence: 99%